A Fixed Effect Panel Spatial Error Model in Identifying Factors of Poverty in West Java Province. Issue 1 (February 2021) - Sudartianto,; Firman,; Suparman, Y.; Ginanjar, I.
Abstract: In the last five years, poverty had been a major problem in West Java Province (WJP). Hence, it becomes a strategic development issue for the next five years. To contribute in eradicating the poverty, we aimed this study at identifying poverty factors and measuring their effects. There are two issues in modelling poverty in WJP. First, there was spatial dependency in poverty among regions. Second, due to data limitation, some important factors were not included in the empirical model. Both might lead to bias in regression parameter estimates. Accordingly, we applied a fixed effect panel spatial error model on the poverty rate in WJP. We found that health and economic welfare effected poverty.